Deposition and reduction of infinite-layer Sr1−xLaxCuO2 films. (21st April 2015) - Sakuma, Keita; He, Yilun; Ueda, Kenji; Asano, Hidefumi
Abstract: Electron-doped infinite-layer (IL) Sr1− x La x CuO2 thin films were grown on bare and lattice-matched Ba0.55 Sr0.45 TiO3 -buffered LaAlO3 (100) substrates by magnetron sputtering, and their structures and electrical properties were investigated systematically for various deposition and reduction conditions. The a - and c -axis-oriented films were obtained on LaAlO3 and LaAlO3 Ba0.55 Sr0.45 TiO3 substrates, respectively. For the c -axis-oriented films, short-time (<6 min) reduction annealing in vacuum followed by deposition was effective for the removal of excess apical oxygen that was incorporated during deposition. The removal of excess apical oxygen was evidenced by the shortened c -axis and the appearance of superconductivity. However, subsequent annealing led to the elongation of the c -axis and loss of superconductivity. The a -axis-oriented films exhibited a similar behavior, although the time scale of such films for reduction annealing was significantly larger than that of the c -axis films. The implications of these results are discussed in terms of the oxygen sublattice in the IL compound.